A New Historiographical Path: Recovering Arthur Danto’s Narrative - Cascales, Raquel (História da Historiografia: International Journal of Theory and History of Historiography, 2024)
This article proposes Arthur Danto’s ‘analytical narrativism,’ and his conceptualization of history as representation, as an unexplored path which can be an alternative to the development of postnarrativism from Hayden White’s ‘figurative realism.’ Danto’s historiographic can shed some light on postnarrativism and on the present-day dilemmas which cloud the academic debates around the writing of history. The article also highlights the need for interdisciplinary dialogue.